Financial Management In Public Health Systems: A Review Of Literature On Funding, Budgeting, And Resource Allocation - Zainal Abidin; Surya Sevi Wijayanna Lumban Tobing (STIKES Columbia Asia Medan, 2025)
This study examines the financial management practices in public health systems, focusing on funding, budgeting, and resource allocation. The objective is to explore the relationship between financial management strategies and healthcare service quality, particularly in low- and middle-income countries. A literature review methodology was used to analyze various studies published between 2010 and 2023. The findings indicate that stable funding, transparent budgeting, and efficient resource allocation significantly enhance healthcare outcomes. These practices ensure that critical services, such as maternal and child health care, are prioritized, thereby improving access to essential services. The study highlights the importance of adopting comprehensive financial strategies to address challenges in public health systems. The implications of this research emphasize the need for policy reforms to improve financial management practices, particularly in resource-limited settings. Future research should investigate the specific financial strategies that can be applied to enhance healthcare delivery in diverse healthcare environments.